Food and migraine in adolescents - Magda Bouhairet; Muhammad Ali; Bistok Saing; Johannes Harlan Saing; Yazid Dimyati (Paediatrica Indonesiana, 2011)
Background Migraine headaches are a common problem worldwide, especially in adolescents. They are usually chronic, with frequent relapses. Therefore, any dietary risk factor for headaches has important implications on migraineurs. However, the association between migraine and diet needs to be examined further.Objective To investigate the association between diet and migraine in adolescents.Methods We conducted a cross-sectional study in August to September 2009 on 13 - 18 year old adolescents in a senior high school in Medan, North Sumatera. We included subjects diagnosed with migraine, according to the International Headache Society (IHS) criteria. Ninety participants completed the questionnaire. Foods we observed for a link to migraine included milk, chocolate, ice cream, cheese, bread, instant noodles, meatballs, chili sauce, sweetener, yoghurt, pizza, and other foods and beverages.Results Of the 90 participants with migraines, there were more females (61.1%) than males. There were statistically significant associations between migraine and triggering foods (P = 0.045, 95% CI 0.59 to 0.79) as well as between migraine and family history of migraine (P = 0.043, 95% CI 0.46 to 0.66). Stress (P = 0.164), menstruation (P = 0.369), and sound or light (P= 0.577) had no significant association with migraine. A wide variety of foods and beverages were implicated as migraine precipitants. The most common were chili sauce (75.8%), ice cream (71.0%), milk (67.7%), instant noodles (67.7%), chocolate (61.3%), peanuts (59.7%), cheese (54.8%) and meatballs (54.8%).Conclusion Food and family history have a significant association with the occurrence of migraine in adolescents.Â